Referendum lokalne w trybie art. 170 ustawy zasadniczej : studium przypadku - Kordik, Anna (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
This article covers the subject area of the local referendum under the Basic Law. In the plane of this dissertation are presented the terminological concept of the term in the etymology of the word as well as the statutory definition. In the second part of the article, the historical concept of shaping this institution has been normalized, both in the spheres of individual epochs and in the regulation of the so-called “Small Constitution” and the work of the National Committee for the Improvement of the Constitution. The referendum of the countries of Europe and the world has also been discussed, taking into account international and EU law. In the penultimate section of this article, there are raised issues of interpretation of Article 170 of the Basic Law with the regulation of special law, including the case law. At the final deduction stage, the statistics for the local referendum on 6 September 2015 were presented, showing the scope of the questions in question and the turnout of the voters in the referendum
Keywords: konstytucja 1997; Europejska Karta Samorządu Lokalnego; referendum lokalne